Acquired Hemophilia A: A Frequently Overlooked Autoimmune Hemorrhagic Disorder - Yoshihiko Sakurai; Tomohiro Takeda (Journal of Immunology Research)
Acquired hemophilia A (AHA) is a rare hemorrhagic disease in which autoantibodies against coagulation factor VIII- (FVIII-) neutralizing antibodies (inhibitors) impair the intrinsic coagulation system. As the inhibitors developed in AHA are autoantibodies, the disease may have an autoimmune cause and is often associated with autoimmune disease. Although acute hemorrhage associated with AHA may be fatal and is costly to treat, AHA is often unrecognized or misdiagnosed. AHA should thus be considered in the differential diagnosis particularly in postpartum women and the elderly with bleeding tendency or prolonged activated partial thromboplastin time. Cross-mixing tests and measurement of FVIII-binding antibodies are useful to confirm AHA diagnosis. For treatment of acute hemorrhage, hemostatic therapy with bypassing agents should be provided. Unlike in congenital hemophilia A with inhibitors, in which immune tolerance induction therapy using repetitive infusions of high-dose FVIII concentrates is effective for inhibitor eradication, immune tolerance induction therapy has shown poor efficacy in treating AHA. Immunosuppressive treatment should thus be initiated to eradicate inhibitors as soon as the diagnosis of AHA is confirmed.